To Comply or Not to Comply: Roma Approach to Health Laws - Pavlikova, Barbara; Freel, Lenka; van Dijk, Jitse P (International journal of environmental research and public health, 2020)
According to the general public in Slovakia, compliance with the law is problematic when it comes to Roma and health. Roma compliance with laws has not yet been studied. The aim of this is study was to explore the determinants of Roma behavior in the field of health laws. We used the concept of a semi-autonomous field proposed by Moore (1973) and the theory of planned behavior by Ajzen (1985). We found that Roma (non-)compliance with health laws was influenced by many different factors, such as beliefs, traditions, living conditions and culture. Group beliefs overrule national laws and also individual preferences, which tend to be subordinate to the group view. The less contact Roma from settlements have with non-Roma, the stronger their own rules are in the field of health. Roma health status is influenced by many factors: group beliefs and community traditions are stronger and overrule individual and state behavioral influence. A community-based participatory approach together with improvement of living conditions in cooperation with Roma is desirable.
Keywords: průřezové studie; Patient Compliance; Roma; zdravotní stav; Cross-Sectional Studies; adherence pacienta; zdravotní politika; Health Status; lidé; Slovakia; Roma health; Romové; Slovenská republika; Health Policy; Humans; non-compliance